2021
DOI: 10.1155/2021/9963824
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning of Schizophrenia Detection with Structural and Functional Neuroimaging

Abstract: Schizophrenia (SZ) is a severe psychiatric illness, and it affects around 1% of the general population; however, its reliable diagnosis is challenging. Functional MRI (fMRI) and structural MRI (sMRI) are useful techniques for investigating the functional and structural abnormalities of the human brain, and a growing number of studies have reported that multimodal brain data can improve diagnostic accuracy. Machine learning (ML) is widely used in the diagnosis of neuroscience and neuropsychiatry diseases, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 69 publications
1
30
0
1
Order By: Relevance
“…A recent study revealed that the use of combined structural and functional measures allows the highest accuracy of classification to detect SZ ( Lei D. et al, 2020 ). However, the input features of previous SZ classification studies were derived from structural and functional neuroimaging features ( de Filippis et al, 2019 ; Shi et al, 2021 ). Our results based on brain network properties further highlight the potential advantages of multimodal features for distinguishing SZ patients from NCs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the use of combined structural and functional measures allows the highest accuracy of classification to detect SZ ( Lei D. et al, 2020 ). However, the input features of previous SZ classification studies were derived from structural and functional neuroimaging features ( de Filippis et al, 2019 ; Shi et al, 2021 ). Our results based on brain network properties further highlight the potential advantages of multimodal features for distinguishing SZ patients from NCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the raw data models, which were residualized of covariates including site, sex, and linear plus quadratic effects of age and head motion (only included for functional models), we observe no group differences after multiple comparison correction. The lack of any group differences in the raw data was initially a puzzling finding due to reported group differences in the literature Arbabshirani et al (2013 ); Cetin et al (2015 , 2016); Dansereau et al (2017 ); Howes et al (2022 ); Lei et al (2020b ,a); Meng et al (2017 ); Rahim et al (2017 ); Rosa et al (2015 ); Salvador et al (2017 ); Shi et al (2021 ); van Erp et al (2018 ); Venkataraman et al (2012 ); Wannan et al (2019 ); Yu et al (2012 ), however, upon investigation of the uncorrected statistical maps, we observe that the raw data follows a similar pattern to the deviation group difference map, but these results do not withstand multiple comparison correction.…”
Section: Resultsmentioning
confidence: 99%
“…Both the two datasets had good classification performance, which further indicated the good classification performance and generalization of our model. Third, it has been reported that combining multimodal data and clinical data can improve the performance of the machine learning model (Shi et al, 2021a;Talai et al, 2021), but the primary set in this study only contained ALFF data. A subsequent study should incorporate other modal MRI data, metrics, and clinical data to construct and evaluate the model.…”
Section: Discussionmentioning
confidence: 97%
“…Resting-state functional magnetic resonance imaging (rs-fMRI), as one of the most commonly used non-invasive techniques in neuroimaging, has been widely used in the diagnosis ( Heim et al, 2017 ; Rubbert et al, 2019 ; Pang et al, 2021 ; Shi et al, 2021a ), monitoring of treatment effects ( Morgan et al, 2017 ; Ge et al, 2020 ), clinical score prediction ( Hou et al, 2016 ), and conversion prediction ( Hojjati et al, 2018 ) in neuropsychiatric diseases. The amplitude of low-frequency fluctuations (ALFF) is one of the most commonly used measurements of rs-fMRI.…”
Section: Introductionmentioning
confidence: 99%